If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 6 = -38 + -1x Reorder the terms: 6 + -5x = -38 + -1x Solving 6 + -5x = -38 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 6 + -5x + x = -38 + -1x + x Combine like terms: -5x + x = -4x 6 + -4x = -38 + -1x + x Combine like terms: -1x + x = 0 6 + -4x = -38 + 0 6 + -4x = -38 Add '-6' to each side of the equation. 6 + -6 + -4x = -38 + -6 Combine like terms: 6 + -6 = 0 0 + -4x = -38 + -6 -4x = -38 + -6 Combine like terms: -38 + -6 = -44 -4x = -44 Divide each side by '-4'. x = 11 Simplifying x = 11
| 10(1-x)-3=47 | | -5(4p-2)=-14+4p | | 1/7+2x/3=(15x-3)/21 | | x+2(4x-13)+9=3(x-5)+4(x-4) | | 133=(3x-2)7 | | 4+8(k+1)=36 | | 5(y-4)/3=2y-5/3 | | 5(y-4)=2y-5/3 | | 3x-4-2x=-13 | | 18=-4a+10 | | (3/7)x-(1/3)x=(4/9)x+1 | | 6y-7+10y=8 | | -16=-a-2+8a | | -13=3.9+z | | 8x-2(x-3)=6(x+1)+2 | | 3y=1/4x-4 | | -2(v+3)-8v=-7v+15 | | -150-11x=-2x+57 | | 4x^2-2x^2-6+19x=180 | | 6(6/7)/3(3/5)= | | (x/15)-(x-1)/20=3x/4 | | 24=9s-12s | | a+5=bfora | | .5-n+2=3 | | 133=3x-2*7 | | x+.8=.5 | | 0=-21+3x | | 18k+27+2=11k-11k | | -3x+1/3(6+3x)=-10 | | 12x+5y=52 | | x/16+19x/5-13/10 | | (X-2)squared=4 |